2017
DOI: 10.1590/1807-2577.19716
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical properties of orthodontic wires on ceramic brackets associated with low friction ligatures

Abstract: ResumoIntrodução: Poucos estudos investigaram as propriedades mecânicas dos fios ortodônticos em bráquetes cerâmicos associados às ligaduras. Objetivo: O objetivo deste estudo foi comparar a carga-deflexão de fios ortodônticos com seção redonda de 0,016" de aço inoxidável (AI), níquel-titânio (NiTi) e composto de polímero reforçado com fibra de vidro (CPRFV). Material e método: Sessenta espécimes obtidos a partir de 10 arcos pré-contornos seccionados (TP Orthodontics), foram divididos em 3 grupos de 20 de acor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…These findings corroborate with the results of the present study, where SS showed a 1.6 mm deflection limit during the three-point bending representing the most rigid alloy tested. The NiTi and GUMMENTAL® showed 3 mm of displacement, keeping within the elastic bound and indicating higher elastic properties than SS [22,23].…”
Section: Discussionmentioning
confidence: 78%
“…These findings corroborate with the results of the present study, where SS showed a 1.6 mm deflection limit during the three-point bending representing the most rigid alloy tested. The NiTi and GUMMENTAL® showed 3 mm of displacement, keeping within the elastic bound and indicating higher elastic properties than SS [22,23].…”
Section: Discussionmentioning
confidence: 78%